New species of Didemnidae (Tunicata: Ascidiacea) from the tropical coast of Brazil - Da Rocha, Rosana Moreira; Neves, Isabela Monteiro; Gamba, Gustavo Antunes (Zootaxa, 2015)
The family Didemnidae includes 20% of all known ascidians with six genera in the Atlantic. Here, we describe five new species in the Didemnidae from central coastal Brazil. Four species are in the genus Didemnum and were found in Bahia (D. aurantium, D. flammacolor, D. lambertae, D. longigaster), while one Diplosoma (D. citrinum) was found both in Bahia and Espírito Santo.